The multifaceted health impacts of the COVID-19 pandemic - Valerie Gilbert Ulep (Philippine Institute for Development Studies (PIDS), 2021)
Understanding the direct and indirect health consequences of the COVID-19 pandemic is critical in designing a holistic public health response. This study has two objectives. First, we demonstrated the disruption of essential healthcare services using data from selected government facilities. Second, we estimated the productivity losses from direct and indirect health impacts of the pandemic. Validating our earlier study using health insurance claims, our findings showed a sharp decline in admissions and consultations in selected government facilities, particularly among the vulnerable population. Based on our estimates, the long-run costs from productivity losses from direct and indirect health impacts of the pandemic amount to PHP 2.3 trillion (at net present value). Indirect health impacts account for the majority of these costs. Click here to download the discussion paper.
Keywords: 330; COVID-19; health; broad impact